Publicidad digital y comunicación integrada del marketing en empresas de yoga:: netnografía española y mexicana en Facebook - Miranda Hernández, Laura María Elena; Jiménez Terrazas, Carmen Patricia; Ojeda Arredondo, Armando (2022)
The objective of this study is to explain digital advertising and CIM in yoga companies and compare it in Spanish and Mexican companies, through an investigation with a qualitative approach of the netnographic method of the official Facebook pages of two Yoga companies, from the hypothetical deductive perspective and inductive, content analysis was carried out of the most popular conversations of these companies, identified through a report from the Fanpagekarma platform. The results reveal that the use of logo, institutional colors in an aligned, integrated and coherent way, together with the communication of attributes of price, quality and type of service, in this case the styles of yoga, as part of the communication integrated marketing as well as the affective or cognitive attitude of digital advertising, are elements that generate greater interaction or presence among Facebook users of yoga companies